Factors that affecting firm performance mediated by digital transformation in Indonesia’s state-owned enterprises plantation and forestry industries - Surahman, Rini Hardiyanti; Legowo, Nilo (Edelweiss Applied Science and Technology, 2024)
Digital transformation refers to the integration of digital technology into all areas of a business, fundamentally changing the way it operates and adding value to a firm’s performance. This can involve adopting new technologies, reorganizing business processes, and creating a digital culture within the organization. One of the State-Owned Enterprises (SOE) in Indonesia, PT Perkebunan Nusantara III (Persero) with a focus on agriculture and main commodities, namely Palm Oil and Rubber, is carrying out a digital transformation initiative with the aim of improving firm performance. Along the way, the company faced many obstacles related to implementing digital transformation and the large investment costs incurred. This research aims to test the influence of Digital Transformation Leadership, IT Capability, Digital Mindset, Work Culture Change, Organizational Agility, Human Capital and IT Alignment with Business and test the influence of these variables on Firm Performance with Digital Transformation as a mediating variable. This research uses quantitative research methods by distributing online questionnaires via Google Form to 234 company employees who use Digital Farming, GIS and SCADA applications. Data was analyzed using the SEM-PLS analysis method with Smart-PLS Software version 3.3.9. The results of the research show that IT Capability, Work Culture Change, IT Alignment With Business have a positive effect on Digital Transformation. Apart from that, this research also shows the positive influence of Digital Transformation Leadership on Digital Transformation which is mediated by IT Capability and Digital Mindset on Digital Transformation which is mediated by Work Culture Change. Then, research also shows that Digital Transformation has a significant effect on Firm Performance. the research outcomes can serve as valuable insights for what factors influence firm performance mediated by digital transformation in the SOE plantation and forestry industry business cluster in Indonesia.